Cílování inflace v ČR - Volejníková Jolana (Univerzita Pardubice, 2002)
In January 1998 the Czech national bank became the first central bank in a transition country to adopt inflation targeting. The shift to direct inflation targeting was speeded up as for the prerequisties of rate fegime in May 1997. The aim of this work is to explain the system of inflation targeting. The main problem is about conditioned prognosis and about method its creation. There are information about entrance to European union from monetary sphere in the end of article.
Keywords: Česká národní banka; Inflace; vývoj; prognózy